A Kinect-sensor-based Tracked Robot for Exploring and Climbing Stairs. (21st May 2014) - Li, I-Hsum; Wang, Wei-Yen; Tseng, Chien-Kai
This paper focuses on the stair-climbing problem for a tracked robot. The tracked robot designed in this paper has the ability to explore stairs in an unknown indoor environment, climbing up and down the stairs, keeping balance while climbing, and successfully landing on the stair platform. Intelligent algorithms are proposed to explore and align stairs, and a fuzzy controller is introduced to stabilize the tracked robot's movement during the exploration. An inexpensive Kinect depth sensor is the only equipment needed for all the control modes. Finally, experiments illustrate the effectiveness of the proposed approach for climbing stairs.